Enterprise Risk Management in Today's World: Enterprise-Wide Risk Management and Strategy - Louisot, Jean-Paul; Grima, Simon (Emerald Publishing Limited, 2024)
Enterprise Risk Management in Today's Worldexamines enterprise risk management in its past, present and future, exploring the role that directors and leaders in organizations have in devising risk management strategies, analysing values such as trust, resilience, CSR and governance within organizations.